Estado de cosas inconstitucionales en la legislación colombiana (2016)
According to the research, the ECI Law Institution doesn’t have a consecration in the Colombian legal system, and for this reason it has been more a development of the jurisprudence of the Constitutional Court, who creates the ECI figure, in order to improve some groups’ life conditions, adopting the pertinent judicial solutions, respecting the competences orbit and the expertise of the responsible authorities of implementing the corresponding policies, trough documents compelling the linked entities the fulfilling of the orders coming from our honorable constitutional Court and that implies to evidence an advance in the solution put in place regarding the cases pointed out previously. For this reason the documents were written in order to follow up and report periodically the status of the fulfilling of the sentences issued in the ECI orbit, should be emitted by the linked entity. Under the fundamental Rights of human dignity and equality, this institution declares the ECI; but the most important pillar that the Constitutional Court that he/she took for the declaration of ECI was the constitutionalisation of the Fundamental Rights; to be norm of norms; also that it is it is the keeper of those rights. Finally we can say that this artificial figure has as characteristics; that: i) it is a process action that originates from the systematic break of fundamental rights, ii) the bottom decisions, to solve that systematic rupture of fundamental rights involve also authorities of the executive power and legislative, iii) the judicial decisions not only have effects inter-parts, iv) the court has faculties to carry out a follow up and to demand to this authorities the measures to overcome this state of things against the Constitution. Also, we can say that although it is true that the emergence of this institution was one of the most important, original and useful innovations from the contemporary Constitutionalism to the national and international Jurisprudence as visualization mechanism and of conceptualization of flagrant scenarios of massive and serious breaks against the HHRR, it became also visible some vices and inconsistency that the same Constitutional Court does in the statements, in a same way a slow execution of the orders given by the Constitutional Court could be noted.